Stakeholder Theory Perspective in the Risk Identification Process in Village Government - Aditya Pradesa, Hafid; Agustina, Iin; Imam Taufik, Nur; Mulyadi, Deddy (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
The purpose of this article is to explore the idea of ​​the risk identification process in village government from the perspective of stakeholder theory. This article attempts to demonstrate the importance of risk management in village governance by considering what risks can be identified regarding key stakeholders. Stakeholder theory is used as a theoretical basis in exploring the roles and interests of stakeholders related to village governance. Based on the findings drawn from risk identification process, there are nine identified risks from the four main stakeholder categories of village governance. Based on the identification of stakeholders in the village government, it could be proposed that stakeholder management in integrated risk management in the village government can be carried out and increase the effectiveness on risk and stakeholder management and this would prompts further empirical research. Furthermore, future research directions are suggested by enabling the integration of risk management and stakeholders to benefit the management process and outcomes of risk and stakeholders management. There is potential in the effectiveness of risk management in village government through new ways of thinking, analyzing, and then managing risks and integrating them with stakeholders holistically, rather than traditional efforts in each area. In the future, integrating risk management and stakeholders is very challenging, but it can be a new way to improve the performance of village government with the feasibility and benefits that need to be studied further.